Integrating Psychological Insights into Pre-Service Teacher Training - Thanduxolo Peace Mngomezulu; Oluwatoyin Ayodele Ajani (Social Sciences and Education Research Review)
This scoping review investigates the integration of psychological insights into pre-service teacher training, focusing on curriculum design and its impact on learner behaviours in modern classrooms. The study analysed 348 publications, with a final synthesis of 67 peer-reviewed articles published in English between 2010 and 2024. The aim was to identify effective strategies for incorporating psychological principles into teacher education curricula to better prepare future educators for the diverse behavioural dynamics of contemporary classrooms. The review highlights key themes such as the role of cognitive and behavioural psychology in curriculum development, the importance of understanding student motivations, and the effectiveness of various instructional strategies on student engagement and achievement. Findings suggest that integrating psychological insights into teacher training can significantly enhance pre-service teachers' ability to manage and positively influence learner behaviours. The study provides recommendations for curriculum improvements and suggests areas for further research, aiming to contribute to the development of more effective, psychologically informed teaching practices.